TATA RIAS PENGANTIN MINANG DI NAGARI TARAM KABUPATEN LIMA PULUH KOTA - HALIFA AWALTU RAHMI; Vivi Efrianova (Jurnal Tata Rias dan Kecantikan, 2022)
This research aims to 1) explain what form of makeup the bride minang, 2) describes how the technique of installing makeup of the bride minang, 3) reveals what the meaning of the makeup of the bride minang in Nagari Taram. This type of research is qualitative research with descriptive methods. The instruments in this study were researchers themselves and assisted with supporting instruments such as tape recorders, video tapes, or cameras. Data collection techniques are observation, interview and documentation. Measures for analyzing data are data collection, data reduction, data presentation and conclusion drawing. The result of this study is a form of clothing of the bride minang, consisting of talipuak, lambak, drums. For men in pangulu and sarawa gadang clothes. Accessories for women suntiang banana saparak, dukua, galang, ikek waist. Men like deta or saluak, sasampiang, karih, and tungkek. Bridal makeup and bridal make-up techniques in Nagari Taram using solid powder sponges, sow powder sponges, foundation sponges and brushes, starting from foundation, powder sow, solid powder, eyebrow frame, eye shadow, false eyelashes, blush and lipstick. While the installation of clothes starts from the installation of lambak, installing talipuak clothes, scarves and other attributes, then buns, hijabs and banana suntiang saparak. The meaning of bridal make-up in Nagari Taram is very deep and spacious.